Cultural Beliefs and Instructional Intentions: Do Experiences in Teacher Education Institutions Matter?. (June 2018) - Kumar, Revathy; Lauermann, Fani
This cross-sectional study examines associations between preservice teachers' experiences in teacher education ( n = 2, 129), their beliefs about culturally diverse students, and their endorsed instructional practices within social reconstructionist and achievement goal theory frameworks. Structural equation modeling confirmed significant associations between experiences in teacher education and discomfort with student diversity, endorsement of mastery- and performance-oriented practices, and reluctance to adjust instruction to culturally diverse student needs. The number of multicultural education courses completed negatively predicted preservice teachers' stereotype beliefs and positively predicted mastery orientation. Reluctance to accommodate to culturally diverse students' educational needs mediated relations between stereotype beliefs and discomfort with student diversity with mastery- and performance-oriented practices. This demonstrates that general stereotype beliefs can inform proximal cultural intentions and instructional practices.